Influence of graphene nanoplatelets (GNPs) and aluminum-carbon layered double hydroxides (Al-C LDH) in polypropylene matrix of hybrid composite structures on the microstructure and mechanical performances - R. Daulath Banu; R. Karunanithi; S. Sivasankaran; B. Subramanian; Abdullah A. Alhomidan (AIMS Materials Science)
In this study, a polypropylene (PP) matrix was reinforced with ultra-fine graphene nanoplatelets (GNPs), aluminum-carbon layered double hydroxides (Al-C LDHs), and calcium carbonate (CaCO3) as hybrid reinforcements, along with polypropylene grafted maleic anhydride (PP-g-MA) compatibilizers to create a novel thermoplastic-based hybrid composite polymer. The hybrid composite consisted of varying weight percentages of GNPs (ranging from 0.5 to 2.0 wt% in increments of 0.5), 2wt% Al-C LDH, 2wt % CaCO3, and 5wt % PP-g-MA. The bulk samples were manufactured using twin-screw extrusion followed by vertical injection molding. The developed hybrid composites were characterized using high-resolution scanning electron microscopy (HRSEM) for microstructural analysis, X-ray diffraction (XRD) for phase identification, X-ray photoelectron spectroscopy (XPS) for compositional analysis, and Fourier-transform infrared spectroscopy (FTIR) for functional group identification. Thermogravimetric analysis (TGA) was performed to assess thermal stability, crystallization, and melting behavior. Mechanical tests, including tensile, compressive, and three-point bending, were conducted to evaluate mechanical properties, while a low-velocity impact test assessed impact resistance. The results showed that the hybrid composite with a PP matrix embedded with 1.5 wt% GNPs, 2 wt% Al-C LDH, and 2 wt% CaCO3 exhibited improved mechanical properties, achieving an ultimate tensile strength of approximately 45 MPa. This enhancement is attributed to the effective interconnection, bonding, and cross-linking of the reinforcements with the PP matrix, facilitating efficient load transfer, which makes it suitable for structural applications.